Interactive effect of calcined eggshell and montmorillonite on the characteristics of polyvinyl alcohol blends. Issue 4 (9th May 2017) - Bee, Soo‐Tueen; Liew, Shan‐Qi; Ang, Wei; Tin Sin, Lee; Bee, Soo‐Ling; Rahmat, Abdul Razak
Abstract : The objective of this work was to investigate the effect of calcined eggshell and montmorillonite (MMT) on the mechanical‐physico properties and thermal characteristics of the polyvinyl alcohol (PVOH) blends. The increasing of calcined eggshell loading level up to 2 phr has gradually tensile strength of PVOH and PVOH/MMT blends. The MMT particles in PVOH matrix were observed to effectively intercalate into polymer matrix of 2 phr calcined eggshell added PVOH/MMT blends with the increasing of d ‐spacing of deflection peak (002). Scanning electron microscopy images showed that the greater dispersion of calcined eggshell particles in PVOH matrix for both PVOH blends and PVOH/MMT blends at low loading levels of calcined eggshell (<3 phr). The incorporation of low calcined eggshell loading levels (≤2 phr) has significantly increased the melting temperature and enthalpy of melting of PVOH and PVOH/MMT blends, indicating the good interaction effect (intermolecular bonding) between calcined eggshell and PVOH matrix. In conclusion, the addition of calcined eggshell at lower loading levels has significant improvement effect on the mechanical, physical, and thermal properties of both PVOH and PVOH/MMT blends. J. VINYL ADDIT. TECHNOL., 24:324–338, 2018. © 2017 Society of Plastics Engineers